A mechanism for the effect of endocrine disrupting chemicals on placentation. (September 2019) - Yang, Changwon; Song, Gwonhwa; Lim, Whasun
Abstract: Numerous recent studies have shown that endocrine disrupting chemicals (EDCs) in the body of pregnant women can pass through the placenta and be exposed to the fetus, leading to fetal development and cognitive impairment. Placentation through invasion of trophoblast cells and vascular remodeling is essential to maintaining maternal and fetal health throughout the pregnancy. Abnormal placentation can lead to pregnancy disorders such as preeclampsia (PE) and intrauterine growth retardation (IUGR). However, many studies have not been conducted on whether EDCs can inhibit the development and function of the placenta. Isolating placental tissues to analyze the effect of EDCs on placentation has several limitations. In this review, we discussed the types of EDCs that can pass through the placental barrier and accumulate in the placenta with relative outcome. EDCs can be released from a variety of products including plasticizers, pesticides, and retardant. We also discussed the development and dysfunction of the placenta when EDCs were treated on trophoblast cells or pregnant rodent models. The effects of EDCs on the placenta of livestock are also discussed, together with the molecular mechanism of EDCs acting in trophoblast cells. We describe how EDCs cross the membrane of trophoblasts to regulate signaling pathways, causing genetic and epigenetic changes that lead to changes in cell viability and invasiveness. Further studies on the effects of EDCs on placenta may draw attention to the correct use of products containing EDCs during pregnancy. Highlights: Endocrine disrupting chemicals (EDCs) induces apoptotic cell death in placental cells. EDCs reduce invasiveness and proliferation of trophoblast cells during early pregnancy. EDCs might lead to fetal development and cognitive impairment.